Pu-erh tea attenuates smoking-induced foam cell formation through inhibition of the α9-nicotinic-acetylcholine receptor expression in monocytes: An ex vivo study. (April 2016) - Chen, Li-Ching; Chen, Ming-Yao; Tu, Shih-Hsin; Pan, Min-Hsiung; Lo, Chih-Yu; Ho, Chi-Tang; Wu, Chih-Hsiung; Ho, Yuan-Soon
Highlights: Nearly 90% of the α9-nAchR protein was exclusively expressed in monocytes. Nicotine-induced foam-cell formation was significantly observed in monocytes from heavy smokers. Tea consumption downregulated the monocytic α9-nAchR expression which that causes resist nicotine-induced foam cell formation. Tea-drinking effectively attenuates the initial step (foam-cell formation) of smoking-induced atherosclerosis in circulating monocytes. Abstract: To assess whether drinking tea can effectively prevent smoking-induced atherosclerosis, a clinical trial ex vivo study was performed. The volunteers were randomly allocated to two groups (n = 55 per group) that received either Pu-erh tea powder or a cellulose placebo (0.5 g/capsule, T.I.D.) for two months. The circulating monocytes were isolated from the tested individuals after 0, 1, and 2 months of tea-capsule administration. We found that monocytes displaying high α9-nicotinic-acetylcholine-receptor (α9-nAchR) expression that were isolated from heavy smokers before consuming tea capsules tended to form foam cells in response to nicotine (1 µL for 24 h, * P < 0.001). In contrast, long-term tea consumption significantly downregulated the monocytic α9-nAchR expression (0 months vs. 1 and 2 months; # P = 0.013 and ## P = 0.004, respectively) which causes circulating monocytes to resist nicotine-induced foam cell formation even in heavy-smokers (* P < 0.001). This study suggests that tea-drinking effectively attenuates the initial step (foam-cell formation) of smoking-induced atherosclerosis in circulating monocytes.